How does Nursing Students Knowledge and Attitude correlate in relation to Rabies? An institutional based Cross-Sectional study in Assam - Baruah, Chetanjit; Singh, Sadhna (Indian Journal of Community Health, 2022)
Introduction: Rabies is a vaccine-preventable viral disease. Every year, Rabies causes 18 000-20 000 deaths in India and dogs are responsible for 99 % of all human deaths.Objectives: 1) To assess the knowledge and attitude about rabies among the nursing students.2) To assess whether there is any difference of knowledge and attitude about Rabies among different academic year of the nursing students.3) To assess whether there is any relation between scores of knowledge and attitude.Material & Methods: A cross sectional study was conducted among 142 students of B.Sc. Nursing College, Dibrugarh, Assam in January 2022 using Google form containing pre designed structured closed ended questionnaire by convenience sampling. Knowledge and attitude was assessed by a scoring system. Results were expressed in proportion, percentage, mean, standard deviation. ANOVA and Spearman”s correlation was applied. Results: Mean knowledge & attitude score was 15.7±3.6 and 23.6±2.6.Majority (82.4%) of the students had good knowledge about rabies.Almost all (97.9 %) students had positive attitude towards rabies. There was no significant difference between knowledge score and attitude score among different academic year of the students. Knowledge was positively correlated with attitude of the students.Conclusion: The study revealed good knowledge and positive attitude regarding rabies among the students.